Pengaruh belanja modal dan pendapatan asli daerah terhadap fiscal stress melalui pertumbuhan ekonomi - Windhu Putra; Jaka Syahbandi; Irfan Mahdi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to; 1) Test and analyze the influence of capital expenditure growth and Original Local Government Revenue growth on economic growth in the Regencies/Cities of West Kalimantan Province. 2) Test and analyze the influence of capital expenditure growth and regional original revenue growth on fiscal stress through economic growth in the Regencies/Cities of West Kalimantan Province. The study uses the Path Analysis method in the Sobel Test of Panel Data Regression to analyze the direct and indirect effects of capital expenditure growth and regional original revenue growth on fiscal stress through economic growth in the 14 Regencies/Cities of West Kalimantan Province. The conclusion from the study results shows that capital expenditure growth and regional original revenue have different influences on fiscal stress and economic growth in the Regencies/Cities of West Kalimantan Province. Capital expenditure growth has a significant negative impact on fiscal stress, while Original Local Government Revenue growth has a significant positive impact on fiscal stress. However, capital expenditure growth and regional original revenue do not have a significant effect on economic growth in the Regencies/Cities of West Kalimantan Province. Additionally, no mediating influence was found between capital expenditure growth or regional original revenue and fiscal stress through economic growth.